Prospects for Using RNAi as Control for Ants - Allen, Margaret L. (Frontiers in Agronomy, 2021)
The discovery of RNA interference (RNAi) has inspired insect scientists to aim towards the development of this technology for protection against insect pests. The RNAi mechanism works at the intracellular level by exploiting a mode of action specific to the expression of genes, interrupting the transcription to translation process. Many of the limitations of RNAi technology are being addressed to adapt it for insect pest application. However, most of the insect pest problems for which RNAi is being developed involve direct plant-insect interactions, primarily in monoculture crop systems. Ants are important agricultural pests that generally do not feed directly on crops, yet have dramatic impact on agroecosystems. The application of RNAi to pest ants is complicated by the social nature of ants. Here the goal is to examine the potential application of RNAi to ant pests, especially invasive ants, which present distinct challenges with regard to delivery, targeting, efficacy, and risks.